The Influence of Internal Control Systems, BPD Participation dnd The Use of Information Technology on The Accountability of Village Fund Management - Ismawanto, Refsi; Santosa, R. Ery Wibowo A; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
This study aims to examine the effect internal control systems, BPD participation and the use of information technology on the accountability of village fund management either partially or simultaneously. This study uses primary data, and is included in research with a quantitative approach. The population used in this study is apparatus and officials in Kaligondang sub-district. Sampling in this study was by using purposive sampling, with several predetermined criteria. The data in this study was taken using a questionnaire. The results of this study provide evidence that partially the variables of the internal control system, community participation and the use of information technology have an effect on the accountability of village fund management.